Using Participant Feedback to Improve Two Selective Eating Disorder and Obesity Prevention Programs - Shaw, Heather (Eat Behav, 2018)
OBJECTIVE: To examine qualitative feedback from participants of Healthy Weight and Project Health eating disorder/obesity prevention programs to guide refinements to increase program efficacy. METHOD: Feedback was collected from college students with weight concerns randomly assigned to one of these interventions (N=364, 72% female). RESULTS: Healthy Weight participants reported greater program satisfaction (p=.02); no other quantitative differences emerged in opinions of the program or leaders. Project Health participants most valued goal setting (27%), the group setting (23%), and the provided information (16%). Healthy Weight participants most valued the group setting (21%), goal setting (19%), and accountability for behavior change (18%). Project Health participants reported home exercises most frequently as least valuable (22%), followed by role-plays (13%). Healthy Weight participants most frequently reported “nothing” as least valuable (24%), followed by food/exercise logs (9%). The top suggestion from participants from both groups was to add interactive activities. CONCLUSIONS: Weight gain preventive effects of Project Health were stronger, but Healthy Weight participants were more satisfied, perhaps because Project Health incorporates dissonance-induction strategies which produce psychological discomfort that promotes internalization of health lifestyle goals. Both interventions could be made more interactive by adding group exercises, encouraging group connection via social media, and adding icebreakers.